Fluorescent Probes Design Strategies for Imaging Mitochondria and Lysosomes - Chen, Huimin; Yu, Zhenjie; Ren, Shiwei; Qiu, Yuyu (Frontiers in Pharmacology, 2022)
Modern cellular biology faces several major obstacles, such as the determination of the concentration of the active sites corresponding to chemical substances. In recent years, the popular small molecule fluorescent probes have completely changed the understanding of biology through their high sensitivity towards a specific substance in various organisms. Mitochondria and lysosomes are significant organelles in various organisms, and their interaction is closely related to the development of various diseases. The investigation of their structure and function has gathered tremendous attention from biologists. The advanced nanoscopic technologies have replaced the diffraction-limited conventional imaging techniques and have been developed to explore the unknown aspects of mitochondria and lysosomes with a sub-diffraction resolution. Recent progress in this field has yielded several excellent mitochondria- and lysosome-targeted fluorescent probes, some of which have demonstrated significant biological applications. Herein, we review studies that have been carried out to date, and suggest future research directions that will harness the considerable potential of mitochondria- and lysosome-targeted fluorescent probes.